Analysis Of The Influence Of Greenport Implementation On Service User Satisfaction At Pt Terminal Teluk Lamong Gresik Through The Image Of The Port Business Body - Djuliyanto, Djuliyanto; Adi, Desman; Putra Pratama, Aditya; Dwi Kurniawan, Wardoyo (International Journal of Science, Technology & Management, 2024)
Teluk Lamong Terminal is the first semi-automatic terminal in Indonesia with environmentally friendly technology. Teluk Lamong Terminal was built as an implementation of the Tanjung Perak Port Development which is equipped with loading and unloading equipment using modern technology. This research aims to determine and develop the effect of implementing Greenport on service user satisfaction through the image of the Port Business Entity at PT. Lamong Gresik Bay Terminal. The research strategy used in this research is quantitative with an explanatory research approach. The research sample was 155 service users at PT. Lamong Gresik Bay Terminal. The analysis tool used is SPSS for instrument testing and SEMPLS with SmartPLS to answer the problem formulation. The results of the research show that there is a significant positive influence of the application of Greenport on the image of the Port Business Entity. There is a significant positive influence of the application of Greenport on service user satisfaction. There is a significant positive influence of the image of the Business Entity on the satisfaction of service users. The image of the Port Business Entity is able to mediate the implementation of Greenport on satisfaction of service users at PT. Lamong Gresik Bay Terminal. It can be concluded that both directly and indirectly there is an influence of the implementation of Greenport on service user satisfaction through the image of the Port Business Entity at PT. Lamong Gresik Bay Terminal.